A study to assess select risk factors for carcinoma cervix among patients attending Kidwai Memorial Institute of Oncology - M., Swapnajaswanth; S. P., Suryanarayana; G., Suman; N. S., Murthy (International Journal Of Community Medicine And Public Health, 2017)
Background: Cervical cancer is an important public health problem worldwide; it is second most common cancer among women aged 15-44 years globally (Globocan 2012). The objective of the study was to study the association between select risk factors and carcinoma cervix among patients attending Kidwai Memorial Institute of Oncology, Bangalore. Methods: Hospital based case- control study was carried among newly diagnosed cases of cervical cancer, cases and apparently healthy controls were selected. Statistical analysis was performed using, Chi square test of significance, logistic regression were preformed. Results: Univariate analysis revealed the following variables as significant risk factors these were Age at consummation of marriage <18 years OR 5.9 (2.6-19.4), Age 1st pregnancy <18 years OR 3.4 (2.2-5.2), live births delivered >5 OR 2.9 (1.7-5.8), marital status other than those who were married OR 1.7 (1.2-2.6), education of study subject being uneducated OR 3.9 (2.9-5.7), not washing genitals after sex OR 2.8 (1.6-4.9), material used during menstruation other than sanitary pads OR 6 (3.1-11.7), sex during menstruation OR 3 (1.1-7.9), not washing of private parts daily OR 10.8 (6.4-18.2), not taking bath daily OR 4.4 (2.8-7), open air defecation 7.6 (5.4-11.7), tobacco use OR 3.3 (2.2-5.6), never use of any contraceptive OR 3.7 (1.0-8.3) were significant at 0.05 level. Following backward multiple logistic regression analysis the following variables were independently associated with the development of cancer cervix, these were, age at 1st pregnancy <18 years OR 2.2 (1.2-3.8), use of material other than sanitary pads OR 3 (1.3-6.5), having sex during menstruation OR 4.3 (1.2-15), not washing of private parts daily OR 5.5 (2.9-10.4), open air defecation OR 2.6 (1.4-4.7), attained significance at 0.05 level. Conclusions: The study has revealed that age at 1st pregnancy <18 years, use of material other than sanitary pads, having sex during menstruation, not washing of private parts daily, open air defecation, as an independent risk factor for the development of cancer cervix. It can be noted that all the risk factor mentioned above is highly amenable for primary prevention.